Analisis Tingkat Motivasi Belajar Siswa Dalam Pembelajaran Daring Pada Mata Pelajaran Matematika - Nanda Ayu Sasami; Krisdianto Hadiprasetyo; Erika Laras Astutiningtyas (Absis: Mathematics Education Journal, 2021)
The purpose of this study was to find out how the level of sudent motivation in online learning in mathematics in class XI MIPA SMA Negeri 1 Weru in the academic year 2019/2020 and to find out how students’ motivation to learn in each indicator. This research uses descriptive method with a qualitative approach. Data collection techniques used in this study in the form of a questionnaire. The result showed that the level of student motivation in online learning in mathematics in the class XI MIPA of SMA Negeri 1 Weru in academic year 2019/2020 was included in the medium category. With the percentage of students’ motivation in each indicator that is in indicator 1 (Perseverance in doing the assignment) of 66,53% so that it is included in the sufficient category, in indicator 2 (Resilient in facing difficulties) by 69,19% so that it is included in the sufficient category, at indicator 3 (Happy working independently) by 68,01% so that it is included in the sufficient category, in indicator 4 (There is encouragement and needs in learning) by 67,47% so it is included in the sufficient category, indicator 5 (Showing interest) 0f 55, 38% so it is included in the category of not good, in indicator 6 (Can maintain confidence) of 69,35% so that it is included in the sufficient category, in indicator 7 (Happy to find and solve answers to mathematical problems) of 64,11% so that it is included in enough categories.